Do liquidity, solvency, and profitability affect technology firm growth? Evidence from Indonesia - Winda Purnamasari; Suhardi Suhardi; Jufrisani Akbar (Lembaga Riset Mutiara Akbar (LARISMA), 2026)
This study aims to analyze the influence of liquidity, solvency, and profitability on the growth of technology companies listed on the Indonesia Stock Exchange during the 2020–2024 period. The study used a quantitative approach with panel data obtained from the annual financial reports of 47 technology companies, resulting in 235 observations through a purposive sampling technique. Liquidity was proxied using the Current Ratio (CR), solvency using the Debt to Equity Ratio (DER), and profitability using Return on Assets (ROA), while company growth was measured using asset growth. Data analysis was conducted using panel data regression with a Fixed Effect Model selected based on the Chow and Hausman tests. The results showed that partially, liquidity, solvency, and profitability did not significantly influence the growth of technology companies. However, simultaneously, all three variables significantly influenced company growth, indicating that overall financial condition remains important in supporting company expansion. The coefficient of determination value indicates that the model is able to explain most of the variation in company growth. This finding indicates that technology company growth is more influenced by company-specific characteristics, innovation strategies, and digital business models than individual traditional financial ratios.